KOORDINASI ANTAR TIM DALAM PELAKSANAAN ALOKASI DANA DESA DI DESA KARYA BARU KECAMATAN MARAU KABUPATEN KETAPANG - Yose Fina Andini E.42009025 (FISIP Universitas Tanjungpura Pontianak, 2013)
This essay aims to identify and analize the effectiveness of coordination among teams in the execution of funds allocation for village in Karya Baru Village Marau District in Ketapang Regency. The title is choosen baseissues that there are some developments that haven’t finished by the year of funds allocation. This study uses a descriptive type of research with a qualitative approach. This study was conducted through the steps of research such as literature research which includes collecting and obtaining the theories used as a foundation in research and field research in the form of obtaining data directly. Theory that used to analyze is from Tripathi and Reddy about some conditions to achieve efective coordination, such as first chance, continuity, formulation of authority and responsibility, efective communication, and efective leadership. The conclusion of this study is coordination in execution of funds allocation for village in Karya Baru Village has gone on well overall, but there are several obstacles, such as certain people who are not incapable of implementing their competence and responsibility, leadership of village headman which lack of giving guidelines and motivations, and a lack of incentive. Keywords : Coordination, Funds Allocation For Village, Effectiveness